Applying the Theory of Confidence in Correctional Guidance and Counseling: A Case Study on Self-Confidence and Reintegration in Indonesia - Maulana Riqfi Zaein; Denok Setiawati; Evi Winingsih (Universitas PGRI Yogyakarta, 2026)
Self-confidence is an important aspect of Guidance and Counseling services for Correctional Facility Inmates, supporting the guidance and preparation for social reintegration. Good self-confidence supports decision-making, relationship building, and adaptation, while low self-confidence triggers anxiety and pessimism about the future. This study aims to explore the application of the Theory of Confidence to improve inmates' self-confidence at the Gresik Class IIB Detention Center. The research used a qualitative approach with a single instrumental case study design. Data were collected through in-depth interviews, observations, and document reviews, then analyzed using the interactive model of Miles, Huberman, and Saldaña through the stages of data condensation, presentation, and conclusion verification. The results of this study indicate that applying the Theory of Confidence plays a significant role in social reintegration, thereby reducing the risk of recidivism. Supporting factors include positive reinforcement through motivation and feedback, opportunities for self-actualization through religious programs, skills training, involvement in work activities, and social support in a conducive foster care environment. Meanwhile, inhibiting factors include fear, shame, difficulty adapting, social stigma, lack of family support, and excessive guilt. This study provides evidence-based recommendations for policymakers and practitioners on designing humane rehabilitation programs to strengthen social reintegration readiness and minimize the risk of recidivism. Keywords: correctional inmates, guidance and counseling, theory of confidence, self-confidence, social reintegration